What men do when a baby cries : increasing testosterone may lead to less nurturant care but more environmental vigilance - Setoh, Peipei (2019)
Infants’ crying modulates parental behaviors, which in turn, ideally, lead to calming the infant. The mutually beneficial reciprocity between infants’ and parents’ behaviors is conserved across mammalian species. Although some studies highlight similarities in responses to infant cries across gender, other studies report differences in their behaviors and brain activity. Zeifman and colleagues in this Special Issue found that high levels of infant crying can trigger increases in testosterone in men, which is accompanied by less sensitive caregiving. Some interpret males’ lack of sensitive caregiving as neglectful, but these results could be considered as evolutionarily adaptive. Specifically, increases in testosterone levels from intense infant cries could lead to increased vigilance and alertness toward external stimuli, and thus allow males to be better equipped to protect their young.